INDUCED MATURATION AND SPAWNING OF INDIAN PENAEID PRAWNS - Muthu, M S; Laxminarayana, A (Indian Journal of Fisheries, 2011)
Penaeid prawn hatcheries are being established in many parts of theworld 10 meet the great demand for quality prawn seed for coastal aquaoulture.A steady supply of spawners is essential for efficient programming of the hatcheryoperations. As the collection of spawners from the sea is a costly and uncertainoperation, efforts have been made to induce the captive broodstock tomature under controlled conditions